Time Trends and Predictors of Abnormal Postoperative Body Temperature in Infants Transported to the Intensive Care Unit - Hedwig Schroeck; Angela K. Lyden; Wendy L. Benedict; Satya Krishna Ramachandran (Anesthesiology Research and Practice)
Background. Despite increasing adoption of active warming methods over the recent years, little is known about the effectiveness of these interventions on the occurrence of abnormal postoperative temperatures in sick infants. Methods. Preoperative and postoperative temperature readings, patient characteristics, and procedural factors of critically ill infants at a single institution were retrieved retrospectively from June 2006 until May 2014. The primary endpoints were the incidence and trend of postoperative hypothermia and hyperthermia on arrival at the intensive care units. Univariate and adjusted analyses were performed to identify factors independently associated with abnormal postoperative temperatures. Results. 2,350 cases were included. 82% were normothermic postoperatively, while hypothermia and hyperthermia each occurred in 9% of cases. During the study period, hypothermia decreased from 24% to 2% (p<0.0001) while hyperthermia remained unchanged (13% in 2006, 8% in 2014, p=0.357). Factors independently associated with hypothermia were higher ASA status (p=0.02), lack of intraoperative convective warming (p<0.001) and procedure date before 2010 (p<0.001). Independent associations for postoperative hyperthermia included lower body weight (p=0.01) and procedure date before 2010 (p<0.001). Conclusions. We report an increase in postoperative normothermia rates in critically ill infants from 2006 until 2014. Careful monitoring to avoid overcorrection and hyperthermia is recommended.